If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + 9 = 23 Reorder the terms: 9 + 7b = 23 Solving 9 + 7b = 23 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 7b = 23 + -9 Combine like terms: 9 + -9 = 0 0 + 7b = 23 + -9 7b = 23 + -9 Combine like terms: 23 + -9 = 14 7b = 14 Divide each side by '7'. b = 2 Simplifying b = 2
| 18-c=11 | | 9x^2+12xy+4y^2= | | 9x=5x-12 | | -6-21=3p-12 | | 0.4(x+5)-0.3x=1 | | 3x-(x-3)=13 | | 8(x+7)=136 | | 12x=16x | | Y-16=-3 | | 3x-4=3x-4 | | -22=4x-4(x+6) | | c-5=25 | | 2.5=.05x | | 2-4x=3x+7 | | 4x^2+10x-96=0 | | c+15=4c-45 | | x^2-17x+66=0 | | 55-x=21 | | 5-c=25 | | 2x^2+2xy-3x-3y= | | 7(n+4)=21 | | 5-m=12 | | 4-(2x-8)=12 | | 3(n-5)=-2 | | 0=(2x-5)(x+3) | | 3a-9=15 | | 4+2(2x-8)=12 | | 5y+3-7y=15 | | k-(-13)=8 | | 8(z+10)+2=98 | | 8x^2+3=3 | | 3c-4c+1=5c+2+e |